2013
DOI: 10.1016/j.healthpol.2013.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency, effectiveness, equity (E3). Evaluating hospital performance in three dimensions

Abstract: There are well-established frameworks for comparing the performance of health systems cross-nationally on multiple dimensions. A sub-set of such comprehensive schema is taken up by criteria specifically applied to health service delivery, including hospital performance. We focus on evaluating hospital performance, using the New Zealand public hospital sector over the period 2001-2009 as a pragmatic and illustrative case study for cross-national application. We apply a broad three-dimensional matrix--efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 26 publications
1
60
0
2
Order By: Relevance
“…This measure reflects the state of the art in nonprofit hospital research in terms of conceptualizing and operationalizing organizational success and its multidimensionality [50]. We chose to collect both subjective and objective measurements of financial and non-financial indicators to account for measurement issues related to both data sources.…”
Section: Measurementmentioning
confidence: 99%
“…This measure reflects the state of the art in nonprofit hospital research in terms of conceptualizing and operationalizing organizational success and its multidimensionality [50]. We chose to collect both subjective and objective measurements of financial and non-financial indicators to account for measurement issues related to both data sources.…”
Section: Measurementmentioning
confidence: 99%
“…In both Chinese and international contexts, existing efficiency studies on health have mainly focused on the institutional level, rather than the system level, that is, taking institutions as analysis units . Hollingsworth reviewed 317 studies on efficiency measurement in the context of health services delivery and found that most studies focused on health institutions .…”
Section: Introductionmentioning
confidence: 99%
“…Many healthcare organizations have recognized that user involvement can improve services quality and safety (Doyle, Lennox, & Bell, 2013;Lawton et al, 2017). Several studies argue that clinical effectiveness, patient safety and patient experiences have to be considered when working on improving care quality (Davis et al, 2013;Doyle et al, 2013;Wells, Campbell, Kumar, Clark, & Jean-Pierre, 2018). Other studies highlight the importance of using patient and stakeholder experiences as a basis for improvement (Davies & Cleary, 2005;Groene et al, 2014;O'Hara, Aase, & Waring, 2018).…”
Section: Backg Rou N Dmentioning
confidence: 99%